Forest characteristics and carbon stock along an elevation gradient in Phulchoki Hill Nepal (Bangladesh Journal of Botany, 2025)
The amount of carbon stored in forests depends on their age, species composition, and geographical locations. This study analyzed the tree species composition and carbon stock in three different forests in different elevation zones of Phulchoki Hill, Nepal. Tree species composition was assessed by quadrat sampling in the forests and carbon stock was determined by using allometric equation. Twenty-three tree species were found in the forests with high tree density and richness in Schima-Castanopsis Forest of Lower zone (1400-1800m). Above-ground tree carbon stock differed significantly among the forest types, ranging from 74.8 t/ha (lower zone) to 404.3 t/ha (upper zone). Tree basal area and biomass carbon stock increased with elevation and Quercus semecarpifolia contributed maximally (94%) to total carbon density at upper elevation zone. Hence, evergreen oak forests at higher elevations contribute to reduce and mitigate climate change by storing significant amount of carbon.Bangladesh J. Bot. 54(2): 177-183, 2025 (June)